2003
DOI: 10.1074/jbc.c300098200
|View full text |Cite
|
Sign up to set email alerts
|

Human Proliferating Cell Nuclear Antigen, Poly(ADP-ribose) Polymerase-1, and p21 /

Abstract: We addressed the analysis of the physical and functional association of proliferating cell nuclear antigen (PCNA), a protein involved in many DNA transactions, with poly(ADP-ribose) polymerase (PARP-1), an enzyme that plays a crucial role in DNA repair and interacts with many DNA replication/repair factors. We demonstrated that PARP-1 and PCNA co-immunoprecipitated both from the soluble and the DNA-bound fraction isolated from S-phase-synchronized HeLa cells. Immunoprecipitation experiments with purified prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 23 publications
4
54
1
Order By: Relevance
“…PARP10 co-purified with PCNA regardless of PARP1 levels. PARP1 also co-immunoprecipitated with PCNA in control cells, as previously shown (45).…”
Section: Parp10supporting
confidence: 80%
See 1 more Smart Citation
“…PARP10 co-purified with PCNA regardless of PARP1 levels. PARP1 also co-immunoprecipitated with PCNA in control cells, as previously shown (45).…”
Section: Parp10supporting
confidence: 80%
“…It was previously shown that PCNA interacts with another member of the PARP family, namely PARP1, to inhibit its ADPribose polymerase activity (45). When we depleted PARP1 using siRNA, we observed that PARP10 co-immunoprecipitated with PCNA to the same extent as in control cells (Fig.…”
Section: Parp10mentioning
confidence: 52%
“…In our system, p21 protein was not completely degraded either at low (2.5 J/m 2 ) or high (10 J/m 2 ) UV doses. In fact, other mechanisms regulating gene expression after UV damage (Barley et al, 1998;McKay et al, 1998), or after other types of DNA lesions (Frouin et al, 2003), may influence p21 turnover. An important factor limiting p21 proteasomal degradation is the interaction with PCNA, because the C8 proteasome subunit binds p21 at its C-terminal region, where the PCNA binding site is located (Touitou et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Associations with PCNA, p53, p21 Waf1/Cip1 , Cockayne syndrome B protein and chromatin assembly factor-1 (CAF-1) (Flohr et al, 2003;Frouin et al, 2003;Okano et al, 2003;Wieler at al., 2003) offer the equally exciting possibility that it is also part of a more general machinery. It will be interesting, therefore, to characterize these associations and determine how PARP-1 and PARP-2 activities and/or the scaffolding properties of poly(ADP-ribose) contribute to the function(s) and composition of these modules.…”
Section: Discussionmentioning
confidence: 99%